Evaluation of communication to general practitioners when opioid‐naïve post‐surgical patients are discharged from hospital on opioids. Issue 6 (27th April 2020) - Tran, Tim; Taylor, Simone E.; George, Johnson; Pisasale, Daisy; Batrouney, Adele; Ngo, Janet; Stanley, Beata; Elliott, Rohan A.
Abstract: Background: To address the opioid crisis, much work has focused on minimizing opioid supply to surgical patients upon hospital discharge. Research is limited regarding handover to primary care providers. The aim of this study was to evaluate the communication of post‐operative opioid prescribing information provided by hospitals to general practitioners (GPs). Methods: This study comprised two components. First, a retrospective audit of discharge summaries for opioid‐naïve surgical patients supplied with an opioid on discharge was conducted to evaluate accuracy of opioid documentation and presence of an opioid management plan. Second, a survey was distributed to GPs to seek their opinions regarding adequacy of communication about hospital‐initiated opioids in discharge summaries, challenges experienced in opioid management and suggestions for improvement. Results: Discharge summaries for 285 patients were audited. Twenty‐seven (9.5%) patients had no discharge summary completed. Of the remaining 258, 63 (24.4%) summaries had at least one discrepancy between the opioid(s) listed and the opioid(s) dispensed. Only 33 (12.8%) summaries contained an opioid management plan. From 57 GP‐completed surveys, 41 (71.9%) GPs rarely or never received an opioid management plan from hospital surgical units and 34 (59.7%) were dissatisfied/very dissatisfied with information provided about opioid supply and management. Qualitative responses highlighted difficulties GPs experience managing opioid treatment for post‐surgical patients after discharge, differing patient expectations and the need to improve communication at times of transition. Conclusion: When opioid‐naive patients are discharged from hospital on opioids, communication from hospitals to GPs is poor. Future interventions should focus on strategies to improve this. Abstract : In the midst of an international opioid crisis, much of the focus has been aimed towards reducing the supply of opioids from hospital settings. Not all patients, however, are oversupplied with opioids and therefore communication to general practitioners is important as they are often tasked with ongoing management. This study evaluates how opioids are communicated to general practitioners.